Molecular Docking and Toxicity from Temulawak Rhizome (Curcuma xanthorrhiza Roxb.) against COX-2 - Meilinda setya praceka; Ellen N. Yunita; Cleopatra D. Semesta; Refitha N. Putri; Nazwa N. Mikdar; Elsa N. Sitinjak; Luthfi U. Setyawati; Muchtaridi Muchtaridi (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Temulawak rhizome (Curcuma xanthorrhiza Roxb.) is a rhizome that comes from the Zingiberaceaetribe. Temulawak rhizome is commonly used as a traditional medicine in Indonesia as an antiinflammatory.The purpose of this study was to provide information on the potential of temulawakrhizome as a COX-2 inhibitor drug candidate and its toxicity to shrimp larvae (Artemia salina Leach.).The methods used are Lipinski Rule of Five prediction, PreADMET, molecular docking, pharmacophorescreening, and BSLT toxicity test. The results obtained show that the lowest Gibbs energy is producedby curcumin (-9.65 kcal/mol), has a pharmacophore hit value, meets the Lipinski rule of five, predictsa good pharmacophore profile, but curcumin has mutagenic properties and is classified as toxic afterbeing tested. with the BSLT method. So that it can be concluded that curcumin has the potential tobecome an anti-inflammatory drug, but further studies are needed and modifications to the molecularstructure of the compound can be carried out so that the tested compound can produce better activity.